Soil cation storage is a key control on the carbon removal dynamics of enhanced weathering - Y Kanzaki; N J Planavsky; S Zhang; J Jordan; T J Suhrhoff; C T Reinhard (Environmental Research Letters, 2025)
Significant interest and resources are currently being channeled into techniques for durable carbon dioxide removal (CDR) from Earth’s atmosphere. A particular class of these approaches—referred to as enhanced weathering (EW)—seeks to modify the surface alkalinity budget to store CO _2 as dissolved inorganic carbon species. Here, we use a reaction-transport model designed to simulate EW in managed lands to evaluate the throughput and storage timescales of anthropogenic alkalinity in agricultural soils in the coterminous U.S. We find that lag times between alkalinity modification and carbon removal can span from years to many decades depending on region. Background soil cation exchange capacity, agronomic target pH, and fluid infiltration all impact the timescales of CDR relative to the timing of alkalinity input, suggesting there is scope for optimization of alkalinity transport through variation in land management practice. However, shifting practices to reduce lag times may decrease total CDR from weathering and lead to non-optimal nutrient use efficiencies and soil nitrous oxide (N _2 O) fluxes. Our results indicate that there may be a large temporal disconnect between deployment of EW and climate-relevant CDR, with important implications for monitoring, reporting, and verifying carbon removal through EW.